SOCIAL IMPACT ASSESSMENT OF A DISPLACED VILLAGE OF KORAPUT DISTRICT, ODISHA, INDIA - Srinivas, B. K.; Kumar Nayak, Jayanta (IJRDO - Journal of Social Science and Humanities Research, 2016)
The concept of development is a historical legacy. Development seeks the welfare of others and implies technical and economic progress. Social impacts are the results of developmental interventions on human environment. Social impact assessment presents an important opportunity to draw cross-cultural encounters arising from project-based development efforts into wider procedures of engagement and negotiation that might address the imbalance in relationships between local communities, project proponents and states. Chikapar village of Semliguda block in Koraput district of Odisha is selected for the present research study. Hindustan Aeronautics Limited falls under the jurisdiction of the study area. The study area not only falls under potential economic impacts zone but also potential social and environmental impacts due to development interventions. The current study will address the unquestioned and unanswered issues of social impact assessment thereby critically analyzing the issues and suggests the mitigating action.